The Empirical Analysis of Islamic Finance on Economic Growth in Nigeria: an ARDL bounds testing approach - Abubakar Sadiq Salisu; Musa Munkaila; Abubakar Abdullahi (International Journal of Emerging Issues in Islamic Studies, 2022)
Islamic finance model has been a cause of paradigm shift in global financial system because of its capacity to propel economic growth even in the face of global financial crisis and recent Covid-19 pandemic. This study intends to empirically examine the short run and long run impact of islamic modes of finance on economic growth in Nigeria. The study employs autoregressive Distributed lag (ARDL) and Error correction model to explore the relationship using quarterly data from 2013Q4 to 2020Q4. The result of the bound test indicates the presence of long run relationship between islamic modes of finance and economic growth in Nigeria, it also reveals that Murabaha have both long run and short run positive impact while Qardhassan modes of finance have only positive long run impact on economic growth. The result also shows that istisna and ijara modes of finance were found to have insignificant impact on economic growth.